Classical diseases revisited: transient global amnesia. Issue 978 (2nd April 2007) - Owen, D; Paranandi, B; Sivakumar, R; Seevaratnam, M
Abstract : Transient global amnesia usually affects patients between the ages of 40 and 80. Patients with this condition are often described – wrongly – as being confused. It presents classically with an abrupt onset of severe anterograde amnesia. It is usually accompanied by repetitive questioning. The patient does not have any focal neurological symptoms. Patients remain alert, attentive, and cognition is not impaired. However, they are disoriented to time and place. Attacks usually last for 1–8 h but should be less than 24 h. It is possible that it may result from different mechanisms such as venous congestion with valsalva-like activities before symptom onset, arterial thromboembolic ischaemia and vasoconstriction due to hyperventilation. Diagnosis may be made safely in the presence of a characteristic collateral history. No specific treatment is indicated for a typical episode.